Analisis Pengelolaan Keuangan dalam Peningkatan Pembangunan di Desa Angkasa Pura - Doni Mhd Hasrul (Journal of Education on Social Science (JESS), 2021)
This study aims to determine village financial management in increasing development in Angkasa Pura Village, Sitinjau Laut District, Kerinci Regency. This research is motivated by several problems such as lack of human resources, people who do not know about the village financial management system, lack of public understanding of village development programs, lack of cooperation and coordination on village development issues whose development goals are to promote and prosper rural communities. The approach used in this study is a qualitative approach. The informants in this study amounted to 7 people. Techniques and data collection in this study in the form of interviews, observation and documentation. The Unit of Analysis is an individual, social group or institution from the Village Apparatus in Angkasa Pura Village, Sireview Laut District. The results showed that village financial management activities were not optimal, especially in the administration and reporting stages, thus hampering the planned activities